An Optimum Design of a Subsonic Aircraft Wing due to the Aerodynamic Loading - Ibtisam J. Ismeal; Mehmet Bakirci; Muhsin J. Jweeg (The Scientific World Journal)
Aircraft designers are mainly interested in finding the level of pressure, stresses, and deformations of the parts of the aircraft wing. In many aviation accidents, the failure of the wing is the main cause of disasters, as it is considered the main surface that generates the necessary lift for the aircraft in addition to its other functions in controlling the transverse stability. In this work, a numerical study was performed to obtain the optimum wing structural design parameters for high strength and minimum weight for the L-39 A/C wing. The wing was modeled as a honeycomb with different thicknesses using the software SOLIDWORKS 2020. The pressure distribution was predicted using the FLUENT 2022 R1 package. Having obtained the aerodynamic pressure, the deformations and stresses were obtained using the ANSYS program. The results were compared with other researchers using other models, such as using ribs and stringers in the interior structure of the wing. The current results were found to be reliable and acceptable from the design point of view of the high stiffness-to-weight ratio.